2021
DOI: 10.3389/fmicb.2021.756752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi on Rice Growth Under Different Flooding and Shading Regimes

Abstract: Arbuscular mycorrhizal fungi (AMF) are present in paddy fields, where they suffer from periodic soil flooding and sometimes shading stress, but their interaction with rice plants in these environments is not yet fully explained. Based on two greenhouse experiments, we examined rice-growth response to AMF under different flooding and/or shading regimes to survey the regulatory effects of flooding on the mycorrhizal responses of rice plants under different light conditions. AMF had positive or neutral effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…Inoculation of tomatoes under F. oxysporum stress can promote the absorption of K, N, P, Ca, Mn, Zn, and other elements), increase chlorophyll and soluble sugar content, and increase the number of branches and leaves of the plant. Enhanced biological activity indirectly improves the plant’s tolerance to pests and diseases [ 74 , 75 , 76 ]. A study found that the growth of olives damaged by M. incognita and M. javanica significantly improved after inoculation with AMF, and the biomass increased by 88.9% [ 77 ].…”
Section: The Mechanism Of Amf Improving Plant Disease Resistancementioning
confidence: 99%
“…Inoculation of tomatoes under F. oxysporum stress can promote the absorption of K, N, P, Ca, Mn, Zn, and other elements), increase chlorophyll and soluble sugar content, and increase the number of branches and leaves of the plant. Enhanced biological activity indirectly improves the plant’s tolerance to pests and diseases [ 74 , 75 , 76 ]. A study found that the growth of olives damaged by M. incognita and M. javanica significantly improved after inoculation with AMF, and the biomass increased by 88.9% [ 77 ].…”
Section: The Mechanism Of Amf Improving Plant Disease Resistancementioning
confidence: 99%
“…S3 ). Studies of different crop species have shown that the mycorrhizal growth responses are affected by crop species, crop varieties, AMF species, soil fertility and growth conditions (Bernaola and Stout 2019 ; Campo et al 2020 ; Eo and Eom 2009 ; Li et al 2006 , 2018 ; Wang et al 2016 , 2021 ). For example, in Li et al ( 2018 ), the biomass and nutrient content in mycorrhizal wheat were significantly lower than mock-treated plants which might be attributed to high plant density and competition of nutrients between AMF and plants under low nutrient treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that AMF are rare or absent in the rice roots of flooded paddy fields [12,13], while an increasing number of studies have demonstrated the presence of AMF colonization inside rice roots in paddy fields [14][15][16][17]. The mycorrhizal growth response of rice plants differs, ranging from positive to negative [4,[18][19][20][21][22][23][24].…”
Section: Amf In the Paddy Fieldsmentioning
confidence: 99%